EMOSI POSITIF KELUARGA - SIMANUNGKALIT, MISRAN (FITRAH:Jurnal Kajian Ilmu-ilmu Keislaman, 2014)
Abstract: The emotions of Father is urge competition for each father in education presses. The Competency of education, ethic readiness, knowledge, and professional of teach group is cualification of father. Keywords: Emotions, Positive, FamilyÂ Abstrak: Emosi seorang Bapak adalah dorongan kompetisi untuk setiap ayah dalam menekan pendidikan. Kompetensi pendidikan, kesiapan etika, pengetahuan, dan profesional kelompok mengajar adalah kualifikasi ayah. Kata Kunci: Emosi, Positif , Keluarga